Consistency of the estimated target weights and ECW/TBW using BIA after hemodialysis in patients between standing and lying-down positions - Gwangho Choi; Ho Joong Yoon; Young Jin Song; Hae Min Jeong; Jae Eon Gu; Miyeun Han; Seok Hyung Kim; Jong-Woo Yoon; Hyunsuk Kim (BMC Nephrology, 2022)
Abstract Background As hemodialysis is administered with the patient lying down, the distribution of body fluid is stable in the lying position, which is why this position is recommended for bioimpedance analysis (BIA). Although the InBody S10 is widely used for hemodialysis patients in the lying position, clinicians must make the measurements in person. In contrast, patients can use the InBody 770 to obtain measurements by themselves in the standing position, which may be more convenient. Therefore, this study compared the measurements of hemodialysis patients’ estimated target weight and ECW/TBW obtained lying down using the S10 to those obtained in the standing position using the 770. Methods This study was conducted among maintenance hemodialysis patients at Chuncheon Sacred Heart Hospital in October 2020. Measurements from 56 patients before and after hemodialysis were obtained using the 2 machines. Each (S10 or 770) estimated target weight, both pre- and post-hemodialysis, was considered ideal when the ECW/TBW ratio was 0.380. R2 was calculated and the Bland-Altman test was performed. Results The patients’ median age was 64 years old, and 51% were men. The actual ultrafiltration was 2 kg, and the mean TBW change measured using the InBody devices was 1.5 L (R 2 = 0.718) for the S10 and 1.7 L (R 2 = 0.616) for the 770. The estimated target weight at pre- and post-hemodialysis showed a remarkably high correlation with the patients’ actual pre- and post-hemodialysis weight (R 2 > 0.095). The correlation between these measurements (lying vs. standing) before and after hemodialysis was also very close (R 2 = 1.0000). In addition, ECW/TBW had a good correlation (R2 ≥ 0.970) The Bland-Altman test of dry weight and ECW/TBW yielded similar results. Conclusions This study showed that patients’ estimated target weights in the lying position using the InBody S10 device and in the standing position using the InBody 770 device were consistent in both pre- and post-hemodialysis states.